Game-Based Learning for Vocabulary Acquisition: Snake and Ladder and Spelling Bee - Leoni Marlina Fadimpo; Rizqi Claudia Wardani.H (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study examines the effectiveness of combining Snakes and Ladders and Spelling Bee games to improve students’ English vocabulary learning at SMP Muhammadiyah Aimas, Sorong Regency. The study aims to determine whether the integration of these game-based activities can enhance students’ vocabulary mastery, pronunciation, and learning engagement. A quantitative approach was employed using a pre-experimental one-group pre-test and post-test design involving 23 eighth-grade students. Vocabulary mastery was measured using a multiple-choice test administered before and after the treatment. The collected data were analyzed using SPSS version 22 to calculate descriptive statistics and the normalized gain (N-gain) score. The results indicate that students’ vocabulary achievement improved after the implementation of the game-based learning activities. The mean score increased from 76.09 in the pre-test to 83.70 in the post-test, showing a positive change in students’ vocabulary mastery. The N-gain score of 0.31 falls into the moderate improvement category, indicating that the treatment had a meaningful effect on students’ vocabulary learning. These findings suggest that the integration of Snakes and Ladders and Spelling Bee games can support vocabulary acquisition by providing students with opportunities to practice vocabulary in an interactive and engaging learning environment. The Snakes and Ladders game encouraged students’ participation, collaboration, and motivation during classroom activities, while the Spelling Bee activity helped students improve their spelling accuracy and pronunciation. The use of these game-based strategies created a more active and enjoyable learning atmosphere, which contributed to increased student engagement and participation in vocabulary learning. Based on these findings, the study concludes that integrating Snakes and Ladders and Spelling Bee games can be an effective instructional strategy for teaching English vocabulary. Therefore, English teachers are encouraged to incorporate interactive game-based activities into their teaching practices to support vocabulary development and create more engaging language learning experiences.